USING PHOTO-NARRATIVES TO EXPLORE THE CONSTRUCTION OF YOUNG MASCULINITIES - Langa, Malose (PINS-Psychology in Society, 2025)
This article illustrates the use of photo-narratives to explore a group of adolescent boys’ constructions of young masculinities. The boys were from Alexandra Township, an historically working-class and black community in Gauteng. The participants in this study were provided with disposable cameras to take 27 photographs using My life as a boy as the theme. Arrangements were made for the photographs to be collected and processed. In the follow-up interviews, the boys were asked to give a description of each photograph and why and how they had decided to take that photograph to represent aspects of their masculinity. Some of the photographs taken depicted cars, girls, shoes, smoking, drinking, reading books, cleaning and cooking. The photo-narrative method proved useful in allowing boys to represent multifaceted aspects of themselves and their lives and also seemed to highlight both individualised and subjective aspects as well as dominant or normative aspects of masculinity. In talking about their photographs, it is clear that the construction of young township masculinities is characterised by feelings of ambivalence, hesitation and contradiction. The boys in this study seemed to simultaneously comply with and oppose hegemonic norms of masculinity in the narrative images. The boys’ photo-narratives reveal that negotiating alternative voices of young township masculinities is fraught with emotional costs and sacrifices.